Nadawanie nowych znaczeń modernizmowi - Gralinska-Toborek, Agnieszka (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2006)
The contemporary vision of modernism, which is constructed from a point outside of that period, differs from the vision created by the participants and originators of modernism. One of the major problems encountered today is the one of the meaning of modernist works art. The extreme concept of "silent" and "pure" art followed by Clement Greenberg and other modernists has now found itself under criticism. The interpretations of many modern currents in art reveal attempts at identifying new content in works of art, which sometimes seems to be an act of assigning new meaning to art. Such interpretations can be observed in studies of impressionism, cubism, abstract expressionism and minimalism. The problem of meaning is the subject of study of such theorists as Timothy J. Clark, Patricia Leighten, Serge Guilbaut, Rosalind Krauss and W. J. T. Mitchell. Their research concentrates not as much on works of art as on modernists' vision of art. Mitchell shows how theory replaced the content of modernism art and proves that "silent" art is impossible since meanings arise independently of the artist's intention in the process reception. The new vision of modernism does not attempt to create a universal and objective model of that period but instead aims at a multiplication of meanings and at a destruction of the previous model (the holistic model). The vision of modernism comes to resemble a mosaic of unconnected elements.